The Influence of Player Motivation on Problematic Online Gaming of Youth in China: A Mediation Effect of Age - Chaoguang Wang; Fred Charles; Wen Tang (Human Behavior and Emerging Technologies, 2025)
Online game playing of youth in China, especially their problematic online gaming (POG), has become one of the social issues that affects large numbers of people and their families. However, studies about the impact of player’s motivation on problematic playing are sparse and lack systematic approaches. Our current study is aimed at investigating the relationship between gaming motivations and POG. This paper presents the results of a large-scale survey conducted in China with 1557 participants, of whom 1358 (87.2%) were male. A multiple regression analysis with 10 game motivations as predictors has been performed to explore which factors have effects on game addiction. It is shown that the best predictors of game addiction are the escapism motivation, followed by the competition motivation and then the advancement motivation. The mediation effect of demographic variables on the relationships between player’s motivations and game addiction is further examined using the casual steps, and a significant mediating effect of age on game addiction is revealed. The POG differences across gender and age were also examined. The findings enable a better understanding of the underlying mechanics of POG and to minimize the risks and maximise the positive impact of games on society.